2020
DOI: 10.1002/anie.202001609
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of Heritage Objects: Collagen‐Like Triple Helix Found in the Calcium Acetate Hemihydrate Crystal Structure

Abstract: Supporting information and the ORCID identification number(s) for the author(s) of this article can be found under: https://doi.org/10.Communications 9442 www.angewandte.org

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…There are also additional Bragg-peaks present in the recorded diffraction pattern. As they cannot be assigned to any known byproduct such as Ca­(CH 3 COO) 2 ·H 2 O, β-Ca­(CH 3 COO) 2 or Ca­(CH 3 COO) 2 ·1/2H 2 O, and as the elemental analysis indicated the presence of pure anhydrous calcium acetate (calculated: C = 30.4 wt %, H = 3.8 wt %, found: C = 30.4(1) wt %, H = 3.8(1) wt %), we included all measured reflections into the indexing process, which led to a triclinic unit cell of 1090.23(6) Å 3 and the lattice parameters given in Figure a. Heating of the solid to 310 °C led to a drastic change in the diffraction pattern (Figure b).…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…There are also additional Bragg-peaks present in the recorded diffraction pattern. As they cannot be assigned to any known byproduct such as Ca­(CH 3 COO) 2 ·H 2 O, β-Ca­(CH 3 COO) 2 or Ca­(CH 3 COO) 2 ·1/2H 2 O, and as the elemental analysis indicated the presence of pure anhydrous calcium acetate (calculated: C = 30.4 wt %, H = 3.8 wt %, found: C = 30.4(1) wt %, H = 3.8(1) wt %), we included all measured reflections into the indexing process, which led to a triclinic unit cell of 1090.23(6) Å 3 and the lattice parameters given in Figure a. Heating of the solid to 310 °C led to a drastic change in the diffraction pattern (Figure b).…”
Section: Resultsmentioning
confidence: 79%
“…As a consequence, there is a low- and a high-temperature modification of α-Ca­(CH 3 COO) 2 . A comparison with the literature data revealed that HT-α-Ca­(CH 3 COO) 2 (“high temperature” α-Ca­(CH 3 COO) 2 ) has already been observed as an intermediate during the thermal decomposition of both Ca­(CH 3 COO) 2 ­·1/2H 2 O and Ca 3 (CH 3 COO) 4 ­(HCOO) 2 ­·4H 2 O …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The simple acetate anion ([OAc] À ) is ubiquitous in Nature and offers an exciting coordination chemistry because of the plethora of coordination modes it can accommodate with metal ions (Figure 1, right), especially in anionic metal complexes. [1] With larger metal ions such as alkaline earths (Ae 2 + ), lanthanides (Ln 3 + ), or uranyl ([UO 2 ] 2 + ), structurally distinct anionic complexes form structures ranging from isolated monomers chelated by [OAc] À , to dinuclear oligomers and polymeric complexes with chelating, bridging, and mixed coordination modes. [2] Some Ln 3 + ions, for example, Nd 3 + , have been found with up to three different metal/ligand ratios, pointing towards the large hidden potential of these systems to provide unique acetate complexes.…”
Section: Introductionmentioning
confidence: 99%
“…As the amount of substance that can be removed from the artifacts is usually very small, we also describe the synthesis of the corrosion phases by model experiments. In this study we present the characterization and structure elucidation of complex efflorescence salts like Ca2(CH3COO)(HCOO)(NO3)2•4H2O 10 , Ca(CH3COO)(HCOO)•2H2O and Ca3(CH3COO)4(HCOO)2• 4H2O 11 that were found on ancient amphorae (Figure 1, a) or historic birds eggs 5 and seemingly simple corrosion phases like Ca(CH3COO)2•½H2O 12 which crystallizes on marble reliefs (Figure 1, c, d) or ceramics 6 . A systematic structural investigation of these efflorescence phases revealed calcium carboxylate zig-zag chains (Figure 1, b) as the common structural motif, which shows the crucial role of the carboxylic acids in the corrosion processes and explains the great chemical variety of these compounds.…”
mentioning
confidence: 99%